Impact of metals exposure and resiliency values in wild filamentous fungi - Romero, Maria Cristina (2013)
Human activities result in environmental stress produced by heavy metals or organic contaminants, changing the community structure and tolerance. Fungal adaptation to metals, cotolerance and resilience or power to recuperate after being stressed with other factor, had been scarcely studied. The aims of this research were to evalute the Cd-adaptation of soilfungi isolated from contaminated areas, to assess the resistance to cobalt and lead, and to test the resilience ability. Alternaria alternata, Aspergillus conicus, Cylindrocarpon didymum and Gliocladium viride were selected as they developed in Cd-cultures. The Cd-isolated strains removed twice as much Co and Pb than those of the non-polluted parental; and the metal amount removed were correlated with the Cd-concentration. The resiliency resembled their tolerance abilities. A 10-16 % biomass decrease were observed in A. alternata and A. conicus during 10-20 days; whereas a 48-56 % decrease were obtained with C. didymum and G. viride. The Cd-adaptation on the cotolerance development to other metals in A. alternata and A. conicus were a remarkable data, cotolerance to Co and Pb indicated that the mechanisms conferring resistance was not unique for Cd-ions mainly in G. viride and C. didymum. In conclusion, tolerant fungi to Cd, Co and Pb, and resistance developed by repeatedly subculturing the strains with increasing HM levels were obtained. Fungi adapted to metals suggesting that tolerance could also be acquired in natural environments; thus the fungal training to metals could be a remarkable technology for the preservation of any habitats and to implement diverse micoremediation strategies.